Contribution of Motor Ability to Physical Fitness of Elementary School Students - Sepriadi Sepriadi; Syafruddin Syafruddin; Khairuddin Khairuddin; Nurul Ihsan; Liza Liza (Jurnal MensSana, 2022)
Physical fitness is one of the most important things for elementary school students. Students who are fit will easily carry out activities without experiencing fatigue. Many factors affect fitness, one of which is the motor ability of students. This type of research is quantitative research using a correlational research design. The research sample is elementary school students totaling 34 students. The instrument used is the Indonesian Physical Fitness Test to measure students' physical fitness, and Motor Ability with a motor ability test. The data obtained were then analyzed by correlation analysis and simple regression. The results of data analysis showed that Motor ability contributed to the physical fitness of elementary school students by 64.32%, So, it can be concluded that the motor ability contributed to the physical fitness of elementary school students.